REPRESENTASI NILAI DAKWAH PADA FILM AJARI AKU ISLAM (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study examines the value of da'wah contained in the film "Ajari Aku Islam" which aims to identify the representation or depiction of the value of da'wah in the film, through a system of markers and signs, and to find out the reflection of pluralism in people's lives in the film. "Teach Me, Islam".The results showed that the meaning of signs using semiotic analysis in the film "Ajari Aku Islam " by referring to the signifier and the sign (signified) can be observed conceptually. In this film, there are da'wah values that are oriented towards the whole of Islamic teachings including the fields of faith, law and morals which are represented in the form of da'wah Bi Al-Lisan, Bi Al-Qalam, and Bi Al-Hal. There are two points of the representative of the life of pluralism in the film Ajari Aku Islam, namely places and ways of praying.